Quality and innovation policy in the system of provision of administrative services in military educational institutions - PostupnaОlena (Theory and Practice of Public Administration, 2026)
The problem of modernization of the system of provision of administrative services in higher military educational institutions (VVZO) under conditions of martial law and Euro-Atlantic integration is studied. Key issues are related to overcoming the legal asymmetry between civil legislation and military statutes, as well as the adaptation of hierarchical military management to innovative digital tools. The hypothesis of the study is that fragmentary automation of processes without radical reengineering of document routes and the formation of an internal quality policy leads to duplication of functions and an increase in the workload of personnel. Only an integrated approach is able to ensure the speed and safety of service activities. The factual basis was formed by regulatory legal acts of Ukraine, departmental orders of the Ministry of Defense of Ukraine, international quality standards, European recommendations and NATO guidance documents. The methodological framework combines the system analysis method (for studying the service component of the military-military service as an element of the security sector), content analysis and comparative law method (for assessing the regulatory framework), structural-functional method (for modeling the architecture of quality policy) and process reengineering method (for developing digitalization algorithms). The architecture of the internal quality policy of the military-military service is substantiated, which contains strategic, regulatory, resource and monitoring components. Technological tools of digitalization are systematized (automated document flow, integrated accounting databases, secure mobile services). A step-by-step author’s algorithm for modernizing management for the management of the military-military service is developed, which covers the stages from diagnostics and regulatory regulation to practical digitalization and personnel training. The balance of expected benefits and predicted risks that must be taken into account when reforming military education is determined.